Preparation method and application of double-electric-layer waterborne polyurethane coating

Through the electrostatic self-assembly of chitosan-modified graphene oxide and hydrotalcite, double-layer nanosheets are formed, and water-based polyurethane coating is added, which solves the problem of poor compatibility between hydrotalcite and coating, and achieves efficient corrosion resistance improvement, forming A self-healing and anti-corrosion coating with uniform dispersion and good barrier properties is provided.

CN119286372APending Publication Date: 2025-01-10BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410605745.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Hydral talc has poor compatibility with organic resins of coatings, resulting in low barrier properties, making it difficult to obtain a self-healing and anti-corrosion coating with uniform dispersion and good barrier properties.

Method used

Chitosan modified graphene oxide and hydrotalc electrostatically self-assemble to form double-layer nanosheets, and add them to water-based polyurethane coatings. The double-layer coating is formed by repulsive action of homogeneous charges to prevent the penetration of corrosive ions. , enhance anti-corrosion properties.

Benefits of technology

The double-layer structure effectively prevents the penetration of the ions of the corrosive ions from being penetrated, enhances the protective performance of the coating, improves the corrosion resistance, and makes the coating film denser by filling the gaps, blocking the diffusion of corrosive media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286372A_ABST
    Figure CN119286372A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a double-electrode-layer waterborne polyurethane coating, a hydrotalcite-based inorganic double-electrode-layer sheet filler is added into the coating, the double-electrode-layer waterborne polyurethane coating is designed and prepared, and a coating formed by the double-electrode-layer waterborne polyurethane coating has a double-electrode-layer structure. According to the present invention, the comprehensive performance test is performed on the prepared electric double layer coating material, the resistance value of the coating added with the electric double layer material is maximum, the corrosion current is minimum, the corrosion potential is positively shifted from-0.70 V to-0.45 V, and is increased by 250 mV, and the preparation of the electric double layer material can effectively improve the corrosion resistance of the coating. The coating added with the double-electrode-layer two-dimensional nanosheets in different proportions is subjected to a salt spray resistance test, and it is found that the coating added with 5% of the double-electrode-layer two-dimensional nanosheets has the best corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of anti-corrosion materials, and in particular relates to a preparation method of a double-electric layer waterborne polyurethane coating and application thereof. Background Art

[0002] Hydrotalcite is also known as layered double hydroxide (LDH). As a typical layered inorganic functional material, it has important characteristics such as adjustable interlayer metal ion types, inserted anion types and quantities, and interlayer space, and has broad application prospects in the field of metal corrosion protection. Among them, the ion exchange properties of hydrotalcite can be used to embed PO43- between hydrotalcite layers. Utilizing the self-film-forming properties of PO43-, the self-repair of the damaged part of the coating can be successfully achieved, thereby obtaining a self-repairing hydrotalcite coating. Chen et al. embedded the corrosion inhibitor aspartic acid into magnesium-aluminum hydrotalcite and prepared a composite coating on a magnesium alloy using a one-step hydrothermal method. After 20 days of scratching the coating, the exposed substrate was still covered with a protective layer, achieving a self-healing anti-corrosion effect. Li et al. synthesized a magnesium-aluminum hydrotalcite coating in situ on the surface of a magnesium alloy by hydrothermal treatment, and prepared a self-healing anti-corrosion coating by inserting a corrosion inhibitor using ion exchange properties. After 14 days of scratching, the scratches on the coating were significantly healed. Although hydrotalcite has attracted much attention in anti-corrosion, as an inorganic material, hydrotalcite has poor compatibility with organic resins in coatings, and the barrier properties of hydrotalcite itself are still low. Therefore, it is still a huge challenge to obtain a hydrotalcite self-healing anti-corrosion coating with uniform dispersion and good barrier properties.

[0003] In recent years, graphene oxide (GO) has become a research hotspot in the field of environmental protection and corrosion protection due to its high mechanical strength, large specific surface area and excellent barrier properties. There are abundant oxygen-containing groups on the surface of graphene oxide, which provides active reaction sites for chemical modification and is conducive to uniform dispersion in the resin matrix. So far, various modification methods and technologies have been meaningfully studied in the field of graphene oxide composite anti-corrosion coatings. Chitosan is a natural polymer rich in amino and hydroxyl groups and has good corrosion resistance. Therefore, chitosan is an ideal material for modifying graphene oxide and enhancing the corrosion resistance of coatings. Based on this, this study introduces chitosan-modified graphene oxide, and obtains its composite material by electrostatic self-assembly between chitosan-modified graphene oxide and hydrotalcite, thereby increasing the charge density of hydrotalcite. The double-layer two-dimensional nanosheets prepared with chitosan-grafted graphene oxide intercalated hydrotalcite as the matrix are added to the waterborne polyurethane coating. Due to the repulsion of like charges and thermodynamic factors, they tend to be oriented, and the oriented arrangement results in the formation of a double-layer coating. The negatively charged side of the coating can repel corrosive anions (such as Cl-, etc.), and the positively charged side (the layer itself) can repel corrosive cations (such as H+, etc.). Therefore, the coating can actively prevent the penetration of corrosive ions, thereby improving the corrosion resistance of the coating. Summary of the invention

[0004] In order to solve the shortcomings of existing water-based coatings, the present invention is based on the characteristics that hydrotalcite can be easily stripped and the interlayer cations can be replaced. The electrostatic attraction between the cations in the salt solution and the stripped negatively charged hydrotalcite layers is used to synthesize a double-layer nanosheet filler with opposite charges and overall neutrality, and the filler is added to the water-based polyurethane coating as a filler. Since the double-layer filler will be oriented in the water-based polyurethane coating, the like charges will face the same direction, thereby forming a double-layer coating. In addition, this nanosheet is an inorganic crystal, which can also play a role in extending the penetration path of the non-charged corrosive medium in the coating. The main invention contents are:

[0005] A double-electric-layer waterborne polyurethane coating comprises a base material and a filler, wherein the base material is a waterborne polyurethane base material and the filler is a hydrotalcite-based double-electric-layer nanosheet filler.

[0006] A double-electric-layer waterborne polyurethane coating, characterized in that the double-electric-layer nanosheet filler is a double-electric-layer nanosheet filler of chitosan grafted graphene oxide intercalated with phosphate hydrotalcite.

[0007] A double-electric layer waterborne polyurethane coating, characterized in that the chitosan-grafted graphene oxide intercalated hydrotalcite is electrostatically assembled from MAGO, TMCHT and PIH in a mass ratio of 1:1:1.

[0008] A double-electric layer waterborne polyurethane coating, characterized in that the dosage of the double-electric layer nanosheet filler is 0% to 5% of the solid content of the waterborne polyurethane base material.

[0009] Double-layer waterborne polyurethane coatings carry both positive and negative charges, and can rely on the repulsion between charges to prevent the penetration of cationic and anionic corrosive ions, playing an important protective role; and the addition of double-layer nanosheet fillers can fill the gaps in the coating, making it denser, thereby acting as a barrier protective film to block the diffusion of corrosive media and enhance the anti-corrosion properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is the SEM image of Example 4.

[0011] Figure 2 The salt spray images of Examples 1, 2, 3, and 4 are shown.

[0012] Figure 3 Polarization curves are shown in the accompanying abstract. DETAILED DESCRIPTION

[0013] The present invention will be further described below in conjunction with examples and drawings. These examples are merely descriptions of preferred implementations of the present invention, but do not limit the present invention.

[0014] The SEM images in the examples were obtained by scanning the prepared coating using a scanning electron microscope model Suppra55 produced by ZEISS of Germany. The salt spray images were obtained by testing using a salt spray machine model YWXQ-60 produced by Dongguan Lixin Instrument Equipment Co., Ltd. according to the national standard GB / T 6458-86.

[0015] Example 1 (comparative sample, double electric layer filler is 0):

[0016] First, add a certain amount of isophorone diisocyanate and polycarbonate diol to the reactor and react in a water bath at 80°C for 1.5 hours. Then, add 2,2-bis(hydroxymethyl)propionic acid, N,N-dimethylacetamide and dibutyltin dilaurate, and react for another 2 hours at 80°C to obtain a -NCO-terminated prepolymer. The prepolymer is cooled to 45°C, and KH550 with a solid content of 3% is added dropwise to react with it for chain extension. After reacting for 1 hour, triethylamine is added to neutralize the reaction mixture, and acetone is added during the reaction to reduce the viscosity. After 30 minutes, the neutralized reaction mixture is dispersed in distilled water under vigorous stirring, and acetone is removed from the above dispersion under reduced pressure at 30°C to obtain a base coating.

[0017] 15-day salt spray test results are shown in Figure 2 (a), the comprehensive performance test is shown in Table 1.

[0018] Embodiment 2:

[0019] First, add a certain amount of isophorone diisocyanate and polycarbonate diol to the reactor and react in a water bath at 80°C for 1.5 hours. Then, add 2,2-dihydroxymethyl propionic acid, N,N-dimethylacetamide and dibutyltin dilaurate, and react at 80°C for another 2 hours to obtain a -NCO-terminated prepolymer. The prepolymer is cooled to 45°C, and KH550 with a solid content of 3% is added dropwise to react with it for chain extension. After reacting for 1 hour, triethylamine is added to neutralize the reaction mixture, and acetone is added during the reaction to reduce the viscosity. After 30 minutes, the neutralized reaction mixture is dispersed in distilled water under vigorous stirring, and acetone is removed from the above dispersion under reduced pressure at 30°C to obtain a base coating. Recorded as component A.

[0020] A saturated solution of trisodium phosphate dodecahydrate (200 mL) was prepared at room temperature, and magnesium aluminum hydrotalcite powder (2 g) was added thereto. After ultrasonic vibration, the contents were vigorously stirred for half an hour to obtain a uniformly dispersed solution. The solution obtained by suction filtration was washed alternately with deionized water and ethanol, and then dried at 60°C for 4 h to obtain phosphate hydrotalcite (PIH) powder.

[0021] Chitosan was modified with thioformyl dihydrazide using formaldehyde as a coupling agent. At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then chitosan (0.75 g) was added to the solution and stirred continuously. After the chitosan powder was completely dissolved, thioformyl dihydrazide (0.56 g) was added and stirred until the mixture became transparent. After 1 hour, formaldehyde (2 mL) was added, and after complete mixing at room temperature for 12 hours, a mixed solution was obtained. The obtained product was neutralized with an aqueous sodium hydroxide solution to form a precipitate. The precipitate was filtered, washed alternately with deionized water and ethanol, and then vacuum dried at 60°C for 4 hours to obtain thioformyl dihydrazide-modified chitosan (TMCHT) powder.

[0022] Maleic anhydride is grafted onto the surface of graphene oxide through the addition reaction of hydroxyl and epoxy bonds to increase the carboxyl content of graphene oxide. The specific preparation process is as follows: maleic anhydride (7.93 g) is added to deionized water (100 mL), and then graphene oxide (0.32 g) is added. First, stir at 75 ° C for 3 hours and then stir at 85 ° C for 16 hours to obtain a carboxyl graphene oxide (MAGO) mixture. After freeze drying, MAGO powder is obtained.

[0023] At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then MAGO powder and TMCHT powder were added to the dilute acetic acid solution at a mass ratio of 1:1 and stirred at 80 °C for 6 hours to complete the chemical reaction. After freeze drying, graphene oxide powder loaded with chitosan corrosion inhibitor was obtained.

[0024] In addition, PIH powder (200 mg) was dissolved in deionized water (30 mL), and the same mass of MAGO-TMCHT powder was added after ultrasonic ionization for 30 min, and the two mixtures were electrostatically assembled. The obtained powder was denoted as chitosan grafted graphene oxide intercalated hydrotalcite (MAGO-TMCHT@PIH).

[0025] The prepared chitosan grafted graphene oxide intercalated hydrotalcite was first screened and then ultrasonically treated in a formamide (DMF) solution until the Tyndall effect occurred. Then, it was slowly injected into the sodium salt solution through a peristaltic pump and stirred for 12 hours. Finally, the reaction solution was centrifuged, washed and dried to obtain a double-layer two-dimensional nanosheet. It was recorded as component B.

[0026] A double-layer waterborne polyurethane coating can be prepared by adding NaCl solution and weighing 1% solid content of component A to component B.

[0027] 15-day salt spray test results are shown in Figure 2 (b), the comprehensive performance test is shown in Table 1.

[0028] Embodiment 3:

[0029] First, add a certain amount of isophorone diisocyanate and polycarbonate diol to the reactor and react in a water bath at 80°C for 1.5 hours. Then, add 2,2-bis(hydroxymethyl)propionic acid, N,N-dimethylacetamide and dibutyltin dilaurate, and react at 80°C for another 2 hours to obtain a -NCO-terminated prepolymer. The prepolymer is cooled to 45°C, and KH550 with a solid content of 3% is added dropwise to react with it for chain extension. After reacting for 1 hour, triethylamine is added to neutralize the reaction mixture, and acetone is added during the reaction to reduce the viscosity. After 30 minutes, the neutralized reaction mixture is dispersed in distilled water under vigorous stirring, and the acetone is removed from the above dispersion under reduced pressure at 30°C to obtain a base coating. Recorded as component A.

[0030] A saturated solution of trisodium phosphate dodecahydrate (200 mL) was prepared at room temperature, and magnesium aluminum hydrotalcite powder (2 g) was added thereto. After ultrasonic vibration, the contents were vigorously stirred for half an hour to obtain a uniformly dispersed solution. The solution obtained by suction filtration was washed alternately with deionized water and ethanol, and then dried at 60°C for 4 h to obtain phosphate hydrotalcite (PIH) powder.

[0031] Chitosan was modified with thioformyl dihydrazide using formaldehyde as a coupling agent. At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then chitosan (0.75 g) was added to the solution and stirred continuously. After the chitosan powder was completely dissolved, thioformyl dihydrazide (0.56 g) was added and stirred until the mixture became transparent. After 1 hour, formaldehyde (2 mL) was added, and after complete mixing at room temperature for 12 hours, a mixed solution was obtained. The obtained product was neutralized with an aqueous sodium hydroxide solution to form a precipitate. The precipitate was filtered, washed alternately with deionized water and ethanol, and then vacuum dried at 60°C for 4 hours to obtain thioformyl dihydrazide-modified chitosan (TMCHT) powder.

[0032] Maleic anhydride is grafted onto the surface of graphene oxide through the addition reaction of hydroxyl and epoxy bonds to increase the carboxyl content of graphene oxide. The specific preparation process is as follows: maleic anhydride (7.93 g) is added to deionized water (100 mL), and then graphene oxide (0.32 g) is added. First, stir at 75 ° C for 3 hours and then stir at 85 ° C for 16 hours to obtain a carboxyl graphene oxide (MAGO) mixture. After freeze drying, MAGO powder is obtained.

[0033] At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then MAGO powder and TMCHT powder were added to the dilute acetic acid solution at a mass ratio of 1:1 and stirred at 80 °C for 6 hours to complete the chemical reaction. After freeze drying, graphene oxide powder loaded with chitosan corrosion inhibitor was obtained.

[0034] In addition, PIH powder (200 mg) was dissolved in deionized water (30 mL), and the same mass of MAGO-TMCHT powder was added after ultrasonic ionization for 30 min, and the two mixtures were electrostatically assembled. The obtained powder was denoted as chitosan grafted graphene oxide intercalated hydrotalcite (MAGO-TMCHT@PIH).

[0035] The prepared chitosan grafted graphene oxide intercalated hydrotalcite was first screened and then ultrasonically treated in a formamide (DMF) solution until the Tyndall effect occurred. Then, it was slowly injected into the sodium salt solution through a peristaltic pump and stirred for 12 hours. Finally, the reaction solution was centrifuged, washed and dried to obtain a double-layer two-dimensional nanosheet. It was recorded as component B.

[0036] A double-layer waterborne polyurethane coating can be prepared by adding NaCl solution and weighing 3% of component A in solid content to component B.

[0037] 15-day salt spray test results are shown in Figure 2 (c), the comprehensive performance test is shown in Table 1.

[0038] Embodiment 4:

[0039] First, add a certain amount of isophorone diisocyanate and polycarbonate diol to the reactor and react in a water bath at 80°C for 1.5 hours. Then, add 2,2-bis(hydroxymethyl)propionic acid, N,N-dimethylacetamide and dibutyltin dilaurate, and react at 80°C for another 2 hours to obtain a -NCO-terminated prepolymer. The prepolymer is cooled to 45°C, and KH550 with a solid content of 3% is added dropwise to react with it for chain extension. After reacting for 1 hour, triethylamine is added to neutralize the reaction mixture, and acetone is added during the reaction to reduce the viscosity. After 30 minutes, the neutralized reaction mixture is dispersed in distilled water under vigorous stirring, and acetone is removed from the above dispersion under reduced pressure at 30°C to obtain a base coating. Recorded as component A.

[0040] A saturated solution of trisodium phosphate dodecahydrate (200 mL) was prepared at room temperature, and magnesium aluminum hydrotalcite powder (2 g) was added thereto. After ultrasonic vibration, the contents were vigorously stirred for half an hour to obtain a uniformly dispersed solution. The solution obtained by suction filtration was washed alternately with deionized water and ethanol, and then dried at 60°C for 4 h to obtain phosphate hydrotalcite (PIH) powder.

[0041] Chitosan was modified with thioformyl dihydrazide using formaldehyde as a coupling agent. At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then chitosan (0.75 g) was added to the solution and stirred continuously. After the chitosan powder was completely dissolved, thioformyl dihydrazide (0.56 g) was added and stirred until the mixture became transparent. After 1 hour, formaldehyde (2 mL) was added, and after complete mixing at room temperature for 12 hours, a mixed solution was obtained. The obtained product was neutralized with an aqueous sodium hydroxide solution to form a precipitate. The precipitate was filtered, washed alternately with deionized water and ethanol, and then vacuum dried at 60°C for 4 hours to obtain thioformyl dihydrazide-modified chitosan (TMCHT) powder.

[0042] Maleic anhydride is grafted onto the surface of graphene oxide through the addition reaction of hydroxyl and epoxy bonds to increase the carboxyl content of graphene oxide. The specific preparation process is as follows: maleic anhydride (7.93 g) is added to deionized water (100 mL), and then graphene oxide (0.32 g) is added. First, stir at 75 ° C for 3 hours and then stir at 85 ° C for 16 hours to obtain a carboxyl graphene oxide (MAGO) mixture. After freeze drying, MAGO powder is obtained.

[0043] At room temperature, deionized water (30 mL) was added to an acetic acid solution (10 mL), and then MAGO powder and TMCHT powder were added to the dilute acetic acid solution at a mass ratio of 1:1 and stirred at 80 °C for 6 hours to complete the chemical reaction. After freeze drying, graphene oxide powder loaded with chitosan corrosion inhibitor was obtained.

[0044] In addition, PIH powder (200 mg) was dissolved in deionized water (30 mL), and the same mass of MAGO-TMCHT powder was added after ultrasonic ionization for 30 min, and the two mixtures were electrostatically assembled. The obtained powder was denoted as chitosan grafted graphene oxide intercalated hydrotalcite (MAGO-TMCHT@PIH).

[0045] The prepared chitosan grafted graphene oxide intercalated hydrotalcite was first screened and then ultrasonically treated in a formamide (DMF) solution until the Tyndall effect occurred. Then, it was slowly injected into the sodium salt solution through a peristaltic pump and stirred for 12 hours. Finally, the reaction solution was centrifuged, washed and dried to obtain a double-layer two-dimensional nanosheet. It was recorded as component B.

[0046] A double-layer waterborne polyurethane coating can be prepared by adding NaCl solution and weighing 5% solid content of component A to component B.

[0047] The SEM data of the obtained coatings are shown in Figure 1 , 15-day salt spray test results are shown in Figure 2 (d), the comprehensive performance test is shown in Table 1.

[0048] Table 1 Coating properties with different materials added

[0049]

Claims

1. A double-electric layer waterborne polyurethane coating, comprising a base material and a filler, characterized in that: The base material is a waterborne polyurethane base material, and the filler is a hydrotalcite-based double-electric-layer nanosheet filler.

2. The double-electric layer waterborne polyurethane coating according to claim 1, characterized in that: The double-electric-layer nanosheet filler is a double-electric-layer nanosheet filler of chitosan grafted graphene oxide intercalated with phosphate hydrotalcite.

3. The double-electric layer waterborne polyurethane coating according to claim 1, characterized in that: The chitosan-grafted graphene oxide intercalated hydrotalcite is electrostatically assembled by MAGO, TMCHT and PIH in a mass ratio of 1:1:

1.

4. The double-electric layer waterborne polyurethane coating according to claim 1, characterized in that: The dosage of the double-electric layer nanosheet filler is 0% to 5% of the solid content of the waterborne polyurethane base material.